2007
DOI: 10.1080/01932690701283417
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Water/Crude Oil Systems Correlated to the Physicochemical Properties of the Oil Phase

Abstract: A characterization of 30 crude oils has been performed to determine the relative level of influence that individual parameters have over the overall stability of w/o emulsions. The crude oils have been analyzed with respect to bulk and interfacial properties and the characteristics of their w/o emulsions. The parameters include compositional properties, acidity, spectroscopic signatures in the infrared and near-infrared region, density, viscosity, molecular weight, interfacial tension, dilational relaxation, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Variation in surface charges, associated with the mineral composition, cause variation of the local wettability. Surface‐active components of the crude oil may also interact with the aqueous phase and are known to form emulsions (Freedman et al, ; Hannisdal et al, ; Kokal, ; Mandal & Bera, ; McLean & Kilpatrick, ; Opedal et al, ; Paso et al, ; Rezaei & Firoozabadi, ). How such emulsions impact flow behavior is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in surface charges, associated with the mineral composition, cause variation of the local wettability. Surface‐active components of the crude oil may also interact with the aqueous phase and are known to form emulsions (Freedman et al, ; Hannisdal et al, ; Kokal, ; Mandal & Bera, ; McLean & Kilpatrick, ; Opedal et al, ; Paso et al, ; Rezaei & Firoozabadi, ). How such emulsions impact flow behavior is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the study, the waters in contact with the oils were deionized, brine simulating seawater, or simulated process water in flow conditions, , thus leading to the findings that interfacial activity is partly a function of water source and pH. , The crude oils studied were either as received , or they were dissolved in various solvents including n -decane, cyclohexane, , xylene, mixtures of toluene and n -heptane ,,,,,,, (Heptol), or toluene only. ,,,,,,, The latter two solvents are the most commonly used. Also, each study indicated physicochemical properties in keeping with the compositions of oils or oil fractions from sources that included Iran, Brazil, ,, Venezuela, , France, West Africa, , and the Athabasca oil sands. …”
Section: Introductionmentioning
confidence: 99%
“…4,6,11,13,14,18,25,26 The latter two solvents are the most commonly used. Also, each study indicated physicochemical properties in keeping with the compositions of oils or oil fractions from sources that included Iran, 3 Brazil, 12,13,27 Venezuela, 6,14 France, 15 West Africa, 7,21 and the Athabasca oil sands. 28−34 Studies that focused on oil/water interfacial adsorption and rheology often used redissolved asphaltene powder obtained following extraction by n-pentane or n-heptane precipitation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cleaning the produced water reduces the cost and the harm to the environment. In the past, much effort has been devoted to understanding properties of heavy oils, the stability of heavy , and light crude oil emulsions, and heavy-oil emulsion destabilization and its mechanisms. , However, in spite of this body of work, there are still challenges in treating and understanding nanosized emulsions. New tools such as oscillating longitudinal waves, oscillating drop, and capillary pressure methods are now available for studying interfaces, providing the opportunity to gain in-depth insight into the mechanisms while destabilizing the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Cleaning the produced water reduces the cost and the harm to the environment. In the past, much effort has been devoted to understanding properties of heavy oils, [1][2][3] the stability of heavy 1,[4][5][6][7][8] and light crude oil emulsions, [9][10][11][12][13][14][15][16] and heavy-oil emulsion destabilization and its mechanisms. 17,18 However, in spite of this body of work, there are still challenges in treating and understanding nanosized emulsions.…”
Section: ' Introductionmentioning
confidence: 99%